Trypanotolerant cattle and livestock development in West and Central Africa. Vol. I. The international supply and demand for breeding stock - Shaw, A.P.M.; Hoste, Christian H. (1987)
Trypanotolerance and relative productivity of the various breeds existing in West and Central Africa are examined. Possibilities for a wider dissemination and use of these breeds as breeding stock, an increase in their numbers to expand livestock production and availability of animal protein in the tse-tse infested areas are discussed.